Influence of shading on growth, physiological responses and yield of field-grown Habanero chili (Capsicum chinense Jacq.) - Díaz-Pérez, Juan Carlos; Kabir, Md. Yamin; Bashyal, Mamata; Bautista, Jesús; Gunawan, Guna; Núñez-Ramírez, Fidel (Agriculture and Natural Resources, 2026)
Importance of the work: Research on habanero (Capsicum chinense Jacq.) chili production and physiology remain limited, despite their economic and culinary relevance. Objectives: To assess the effects of shade levels on the plant growth, fruit yield, and chemical composition of habanero. Materials and Methods: A two-season field experiment was conducted using five shade levels [0% (unshaded), 30%, 47%, 63%, 80%] and two cultivars (‘Kukulkan’ and ‘Kabal’). The experiment was conducted using a randomized complete block design with 4 replications and 10 treatments, comprising 5 shade levels and 2 cultivars. Response variables were environmental factors, plant height and stem diameter, leaf pigment content, fruit yield, postharvest water loss and fruit soluble solids, total phenolics, flavonoids, antioxidant capacity, and capsaicin concentration. Results: Shade-grown plants were taller and had thinner stems relative to unshaded plants. Shading decreased root-zone and canopy temperatures, lowered evaporative demand and reduced plant water use. Total and marketable yields under 30% and 47% shade were comparable to those under unshaded conditions; however, yields declined significantly at 63% and 80% shade levels. While the number of fruits decreased with increasing shade, the individual fruit weight increased. Kukulkan consistently produced higher total and marketable yields than Kabal. Shading reduced fruit soluble solids, total phenols and antioxidant capacity; however, it did not affect capsaicinoid or carotenoid contents, the incidence of fruit sunscald or blossom-end rot or the postharvest rate of fruit water loss. Main finding: Shading did not increase fruit yields compared to unshaded conditions. However, moderate shading (30% and 47%) did increase individual fruit weight and reduce crop water use. Therefore, moderate shading may be a viable strategy to mitigate environmental challenges without compromising habanero fruit yield or quality.